PREVALENCE OF HYDATIDOSIS IN CAMELUS DROMEDARIUS IN IRAQ - Rahif , R.H.; Al-Fatlawei , M. A.A (The Iraqi Journal of Veterinary Medicine, 2002)
Internal organs of 486 camels were examined, 77 males and 409 females, 2 months - 10 years old, slaughtered at Al-Diwania abattoir from June 2000 till July 2001, for detection the prevelance of hydatid infection. The total rate of infection was 42.18 %, 18.18 % in males and 46.70% in females. Distribution of cysts among organs varied from 13.66 % in livers, 66.34 % in lungs and 20 % in both of them. For the first time in Iraq, Hydatid cyst was recorded in spleen, together with the infection of liver, in one camel. The results of the study showed a higher prevalence of infection among aged camels in comparison with younger animls.